Ekoteologi Islam: Menjelajahi Hubungan Spiritual antara Manusia, Alam, dan Tuhan dalam Tradisi Islam - Alfadhli; Sonia Isna Suratin; Khoirun Nadir; Muhammad Rizqy Fadlillah; Gondo Adhi Saputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to explore the concept of Islamic ecotheology that highlights the spiritual relationship between humans, nature, and God in Islamic tradition. In facing the global environmental crisis, Islamic ecotheology offers a theological perspective that can be a solution to ecological degradation through an approach based on Islamic values. This study uses a literature review method by analyzing various primary and secondary sources, including the Qur'an, Hadith, and the thoughts of Muslim scholars and intellectuals related to Islamic ecology. The results of the study show that Islamic ecotheology emphasizes the concept of tauhid (the oneness of God) as the basis for ecological awareness, amanah (responsibility) of humans as caliphs on earth, and the principles of balance (mizan) and sustainability (istishlah) in maintaining environmental sustainability. The novelty of this study is a systematic mapping of Islamic teachings related to ecology and their relevance in building environmental awareness based on Islamic spirituality, as well as offering a new paradigm in ecotheological studies that connect the normative aspects of Islam with contemporary environmental challenges.